How to help bereaved children - Mohd Adnan, Normala (New StraitsTimes Press, 2021)
Covid-19 brings to attention public policy concerns and their effectiveness in addressing current circumstances, especially children who have lost their parents to the pandemic. Early this week, Malaysia recorded 20,780 new cases, bringing the cumulative Covid-19 infections close to 1.32 million. The death rate stood at 11,373. As this crisis impacts the public, it becomes grimmer for the most vulnerable segments of society, particularly B40 children who have lost their guardians. It is heartbreaking when a guardian or both parents succumb to the pandemic, leaving the children to fend for themselves.